The Importance of the Periods of Growth and Development of the Child's Organism (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
It is known that throughout life a person changes physically and mentally. But in childhood, adolescence and adolescence, development becomes incredibly strong. The child matures as a person in these years, both physically and mentally, due to growth, change.